A New Species of Cryptocoryne (Araceae) from Borneo - Ipor, I.B.; Tawan, C.S; Jacobsen, N. (Gardens' Bulletin Singapore, 2005)
Cryptocoryne zaidiana Ipor & Tawan, a noteworthy new species from Long Tran, Tinjar, Miri Division, Sarawak, is described and illustrated. This amphibious species grows on mudflats in sandy clay soil of the intertidal freshwater zone of Sungai Mering. Its leaf shape and texture are similar to those of Cryptocoryne lingua Engler but differ especially in its spathe characteristics. It has a strongly recurved ovate limb, the upper surface is distinctly covered with purplish and creamy protuberances and it has a distinet creamy collar.